Perancangan Ulang Stasiun Cisauk Kabupaten Tangerang Dengan Pendekatan Teknologi - Rindra Mangkuluhur, Sri; Firmansyah, Rangga; Septony Siregar, Fernando (Telkom University, 2024)
Cisauk Station, located in Tangerang Regency, Banten, faces various challenges related to the lack of supporting facilities and the optimal implementation of information technology. To address this, this study redesigns the interior of Cisauk Station with the concept of a